Determination of retinal nerve fibre layer and ganglion cell/inner plexiform layers progression rates using two optical coherence tomography systems: The PROGRESSA study. (14th August 2020) - Saks, Danit; Schulz, Angela; Craig, Jamie; Graham, Stuart; ,
Abstract: Importance: Glaucoma progression rates may differ depending on the retinal structural parameters measured, and between devices. Background: To compare retinal nerve fibre layer (RNFL) and ganglion cell/inner plexiform layers (GCL/IPL) progression rates using two spectral‐domain optical coherence tomography (OCT) systems. Design: Prospective, university hospital setting. Participants: Cross‐sectional study: 100 eyes from 53 glaucoma suspects and early manifest glaucoma cases. Longitudinal study: subset of 61 eyes from 33 participants. Methods: Same day optic nerve and macular images were acquired using Cirrus and Spectralis systems from which RNFL and GCL/IPL thicknesses were calculated. Longitudinal analysis of RNFL and GCL/IPL progression rates was calculated from 6 × 6‐monthly follow‐up OCT scans. Main Outcome Measures: RNFL and GCL/IPL thicknesses in matched superior, inferior and global regions were compared by both systems cross‐sectionally and longitudinally. Results: At baseline, no RNFL thicknesses differed between devices. Cirrus GCL/IPL regions were significantly thicker than Spectralis ( P  < .001). RNFL and GCL/IPL global progression rates (μm/y) had a mean (SD) of −1.28 (1.11) and 95% CI: (−1.48, −1.09) and −0.51 (0.58) and 95% CI: (−0.62, −0.41), respectively. Progression rates were similar across devices. RNFL loss (%) progressed significantly faster than GCL/IPL, in all regions ( P  ≤ .004). Conclusion and Relevance: Despite baseline thickness differences, overall Cirrus and Spectralis provided similar rates of RNFL and GCL/IPL progression in early glaucoma and can be considered comparable, though not interchangeable, in clinical practice. Further analysis is needed to determine if RNFL progresses faster than GCL/IPL in glaucoma, and whether one precedes the other.